Challenges that contribute to the formation process of primary school principals - Estrada Loya, Cruz Argelia; Villarreal Ballesteros, Ana Cecilia (IE Revista de Investigación Educativa de la REDIECH, 2018)
Training is used as a mechanism to ensure better performance of the professionals. In Mexico the training processes of primary school principals are unclear, and teachers appointed generally occupy the position without academic preparation for leadership roles. This situation has favored principal training and leadership learning happens in their incumbency, and sometimes this learning happens by trial and error. We present this work that was conducted with the objective of analyzing the training processes for principals of primary schools to identify some of the elements that enabled their leadership learning and effectiveness. A multiple case study was conducted using narrative biographical analysis, which identified practical experiences and challenging difficult situations that enable preparation and leadership learning. The study found that exercising authority helps rebuild their professional identity, and this helps principals to learn the function and develop the needed skills for the function. Reported experiences include challenging experiences as organizing the dynamics of school work, the involvement of families in school activities, and obtaining resources to implement actions for improvement. The process found has favoring elements such as in situ learning that practice provides; however, the shortcomings of this approach are that leadership learning occurs in specific situations and mostly by trial and error.